Xbox Kinect™ based rehabilitation as a feasible adjunct for minor upper limb burns rehabilitation: A pilot RCT. Issue 8 (December 2016) - Voon, Kimberly; Silberstein, Ilan; Eranki, Aditya; Phillips, Michael; Wood, Fiona M.; Edgar, Dale W.
Highlights: Interactive video games are growing in their use for burns rehabilitation. Randomised trial comparing Xbox Kinect™ to physiotherapy in burns patients. Exercise time and patient satisfaction significantly increased in Xbox group. Preliminary support for Xbox Kinect™ as an adjunct to burns rehabilitation. Abstract: Introduction: Rehabilitation following burns is integral to improving physical and psychological outcomes. Interactive video game consoles are emerging as therapeutic adjuncts due to their ease of use, affordability, and interactive gameplay. The Xbox Kinect™ has advantage over similar consoles, with controller free interaction utilising three dimensional motion capture software. Player movements during gameplay have been shown to be comparable to completing daily tasks and therefore the Xbox Kinect™ has potential for use as a rehabilitation tool. Aim: The objectives of this pilot study were to compare the efficacy of the Xbox Kinect™ with conventional physiotherapy as an adjunctive tool to promote activity and, to explore their efficacy in influencing functionality and pain. Method: A randomised controlled clinical trial design was used. Intervention group participants were asked to complete two daily 30 min exercise sessions consisting of 15 min of self-directed physiotherapy exercise followed by 15 min of Xbox Kinect™ activities, based on location of burn. Control group participants were asked to complete two daily 30 min exercise sessions of self-directed physiotherapy exercises involving two 15 min sets of exercises, standardised for location of burn. Participants were recruited for a maximum of 7 days. Outcomes assessed included daily activity time, treatment satisfaction, upper limb disability, pain, and self-reported fear of movement (kinesiophobia). Results: A sample of 30 burn patients admitted to Royal Perth Hospital was randomised into intervention and control groups. The intervention group demonstrated significantly greater total activity time compared to control group (median 49.4 and 26.7 min respectively, p < 0.0001), irrespective of total burns surface area (TBSA). Significantly greater satisfaction scores were also demonstrated in the intervention group compared to controls (median 8.53 vs 7.8 respectively, p < 0.0001). There was no evidence to support differences between group measures for upper limb disability, pain and fear avoidance of movement. Conclusion: The Xbox Kinect™ is a useful tool in increasing rehabilitation exercise time and patient satisfaction compared to conventional physiotherapy without indication of concurrent negative effects on patient recovery.